Evaluation of the Power of the Durbin-Watson Statistic for Non-First Order Serial Correlation Alternatives - Blattberg, Robert C. (The Review of Economics and Statistics, 1973)
Robert C. Blattberg, Evaluation of the Power of the Durbin-Watson Statistic for Non-First Order Serial Correlation Alternatives, The Review of Economics and Statistics, Vol. 55, No. 4 (Nov., 1973), pp. 508-515